Co-evolution of marine ecosystems and nutrient cycles during the Great Ordovician Biodiversification Event - Shengchao Yang; Thomas J. Algeo; Thomas Servais; Ronald E. Martin; David A.T. Harper; Charles R. Marshall; Yiying Deng; Zongyuan Sun; Zhengbo Lu; Jian Cao; Chao Li; Shu-zhong Shen; et al. (Earth and Planetary Science Letters, 2026)

Methanobrevibacter smithii induces postnatal growth retardation through blunting hepatic ketone body metabolism - Ming Qi; Tongxing Song; Yuankun Deng; Na Li; Nan Wang; Andong Zha; Qing Ye; Chengming Wang; Yirui Shao; Yucheng Zhu; Ming Sun; Jens Walter; et al. (Science Bulletin, 2026)

The nematicidal activity of Bacillus thuringiensis Cry1Ia36 expressing in Escherichia coli - Feixue Cheng; Dongwei Wang; Jian Wang; Xin Wang; Minzhi Long; Shu-e Sun; Chunhui Zhu; Ju-e Cheng; Xinqiu Tan; Deyong Zhang; Yong Liu (Pesticide Biochemistry and Physiology, 2025)

Screening of Spinal Muscular Atrophy Carriers and Prenatal Diagnosis in Pregnant Women in Yancheng, China - Huilin Sun; Jianli Zheng; Qing’e Zhang; Feifei Ying; Yadong Fu; Yongjuan Guan; Jing Wu; Yueyun Zhou; Jingjing Dong; Mengjun Xu; Fangfang Yang; Ning An; et al. (Biochemical Genetics, 2025)

The association between anthropogenic heat and parent-report symptoms of childhood attention deficit hyperactivity disorder in China: A novel perspective reflecting climate change - Tao Yu; Yue Wen; Pei-Pei Dong; Ming-Kun Sun; Samantha E. Qian; Mario Schootman; Michael G. Vaughn; Shu-Li Xu; He-Hai Huang; Feng-Wen Shan; Shi-Fu Zhu; Jing-Yao Wang; et al. (International Journal of Hygiene and Environmental Health, 2025)

Research landmarks on the 60th anniversary of Epstein-Barr virus - Lan-Yi Zhong; Chu Xie; Le-Le Zhang; Yan-Lin Yang; Yuan-Tao Liu; Ge-Xin Zhao; Guo-Long Bu; Xian-Shu Tian; Zi-Ying Jiang; Bo-Yu Yuan; Peng-Lin Li; Pei-Huang Wu; et al. (Science China Life Sciences, 2025)

Composition, function and succession of bacterial communities in the tomato rhizosphere during continuous cropping - Lv Su; Huatai Li; Jing Wang; Wenting Gao; Xia Shu; Xiting Sun; Kesu Wang; Yan Duan; Yunpeng Liu; Eiko E. Kuramae; Ruifu Zhang; Biao Shen (Biology and Fertility of Soils, 2023)

Identification of general features in soil fungal communities modulated by phenolic acids - Lv Su; Huatai Li; Xiting Sun; Kesu Wang; Xia Shu; Wenting Gao; Yunpeng Liu; Eiko E. Kuramae; Biao Shen; Ruifu Zhang (Applied Soil Ecology, 2023)

Paleoclimatic and anthropogenic impacts on the environment of Southwest China since 33 ka based on multiproxy analysis of karst depression deposits - Xing Tian; Xiaoyong Long; Shu’e Luo; Min Cao; Ji Li; Yuchuan Sun; Sibo Zeng; Ze Wu; Chuan Liu; Lidan Lei; Thomas J. Algeo; Yongjun Jiang (Palaeogeography, Palaeoclimatology, Palaeoecology, 2023)

Initial ingestion of CMV-infected plants reduces subsequent aphid performance - Xiao-bin Shi; Jun Deng; Zhuo Zhang; Shuo Yan; Li-min Zheng; Shu-e Sun; Yang Gao; Xu-guo Zhou; De-yong Zhang; Yong Liu (Arthropod-Plant Interactions, 2021)

Front Cover - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)

Global importance of large‐diameter trees - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)
Aim To examine the contribution of large‐diameter trees to biomass, stand structure, and species richness across forest biomes. Location Global. Time period Early 21st century. Major taxa studied Woody plants. Methods We examined the contribution of large trees to forest density, richness and biomass using a global network of 48 large (from 2 to 60 ha) forest plots representing 5,601,473 stems across 9,298 species and 210 plant families. This contribution was assessed using three metrics: the largest 1% of trees ≥ 1 cm diameter at breast height (DBH), all trees ≥ 60 cm DBH, and those rank‐ordered largest trees that cumulatively comprise 50% of forest biomass. Results Averaged across these 48 forest plots, the largest 1% of trees ≥ 1 cm DBH comprised 50% of aboveground live biomass, with hectare‐scale standard deviation of 26%. Trees ≥ 60 cm DBH comprised 41% of aboveground live tree biomass. The size of the largest trees correlated with total forest biomass ( r 2 = .62, p r 2 = .45, p r 2 = .33, p r 2 = .17, p = .002). The concentration of biomass in the largest 1% of trees declined with increasing absolute latitude ( r 2 = .46, p r 2 = .31, p r 2 = .26, p Main conclusions Because large‐diameter trees constitute roughly half of the mature forest biomass worldwide, their dynamics and sensitivities to environmental change represent potentially large controls on global forest carbon cycling. We recommend managing forests for conservation of existing large‐diameter trees or those that can soon reach large diameters as a simple way to conserve and potentially enhance ecosystem services.

Sedimentary characteristics and model of gravity flow depositional system for the first member of upper Miocene Huangliu Formation in Dongfang area, Yinggehai basin, northwestern South China Sea - Ming Sun; Hua Wang; Jihua Liao; Huajun Gan; Jun Xiao; Jinfeng Ren; Shu’e Zhao (Journal of Earth Science, 2014)